Anisotropy and Temperature Dependence of Myoglobin Translational Diffusion in Myocardium: Implication for Oxygen Transport and Cellular Architecture - Lin, Ping-Chang (The Biophysical Society, 2007)
Pulsed field gradient NMR methods have determined the temperature-dependent diffusion of myoglobin (Mb) in perfused rat myocardium. Mb diffuses with an averaged translational diffusion coefficient (D(Mb)) of 4.24–8.37 × 10(−7)cm(2)/s from 22°C to 40°C and shows no orientation preference over a root mean-square displacement of 2.5–3.5 μm. The D(Mb) agrees with the value predicted by rotational diffusion measurements. Based on the D(Mb), the equipoise diffusion PO(2), the PO(2) in which Mb-facilitated and free O(2) diffusion contribute equally to the O(2) flux, varies from 2.72 to 0.15 in myocardium and from 7.27 to 4.24 mmHg in skeletal muscle. Given the basal PO(2) of ∼10 mmHg, the Mb contribution to O(2) transport appears insignificant in myocardium. In skeletal muscle, Mb-facilitated diffusion begins to contribute significantly only when the PO(2) approaches the P50. In marine mammals, the high Mb concentration confers a predominant role for Mb in intracellular O(2) transport under all physiological conditions. The Q(10) of the D(Mb) ranges from 1.3 to 1.6. The Mb diffusion data indicate that the postulated gel network in the cell must have a minimum percolation cutoff size exceeding 17.5 Å and does not impose tortuosity within the diffusion root mean-square displacement. Moreover, the similar Q(10) for the D(Mb) of solution versus cell Mb suggests that any temperature-dependent alteration of the postulated cell matrix does not significantly affect protein mobility.